The Effect Of Discipline And Responsibility On Employee Performance Mediated By Job Satisfaction A Study At PT. Bromo Logistik Indonesia Ekspres - Moh. Arif Rahman; Ahmad Dzulfikri Budi Kusworo (International Journal of Management and Business Economics, 2026)
This study aims to analyze the influence of work discipline and responsibility on employee performance with job satisfaction as a mediating variable at PT Bromo Logistik Indonesia Express. The study used a quantitative approach with an explanatory research design. Data were obtained through questionnaires, observation, and documentation, then analyzed using validity and reliability tests, classical assumptions, multiple linear regression, and path analysis. The results showed that all research instruments were valid and reliable and met the classical assumptions. Work discipline had a positive and significant effect on employee performance (β = 0.592; p = 0.000), as did responsibility (β = 0.501; p = 0.000) and job satisfaction (β = 0.279; p = 0.032). Simultaneously, work discipline, responsibility, and job satisfaction had a significant effect on employee performance with a coefficient of determination (R²) of 0.595, indicating that 59.5% of the variation in employee performance can be explained by the research model. However, work discipline has a negative and insignificant effect on job satisfaction (β = -0.181; p = 0.310) with an R² value of 0.035. Therefore, job satisfaction is unable to mediate the relationship between work discipline and employee performance because the effect of work discipline on job satisfaction is insignificant.